Magic in the Levant: On Some Late Antique Amuletic Plaque-Pendants - Uscatescu, Alexandra ca. 20./21. Jh. (Bulletin of ASOR, 2025)
The recent translation of an inscribed magical amulet with an Aramaic text found in the macellum of Gerasa (Jerash, Jordan) presents new evidence on magical practices at the end of Late Antiquity and allows for the re-assessment of a particular group of bronze amulets made in the Syrian-Palestinian region. This analysis offers a thorough review of our knowledge about the whole group of amuletic plaque-pendants, especially regarding the syncretic aspects of this craft. Therefore, the following paper proposes to adjust the definition of this group’s features to a new typology.